2021
DOI: 10.1215/00703370-9101102
|View full text |Cite
|
Sign up to set email alerts
|

Under Whose Roof? Understanding the Living Arrangements of Children in Doubled-Up Households

Abstract: A growing literature in family demography examines children's residence in doubled-up (shared) households with extended family members and nonkin. This research has largely overlooked the role of doubling up as a housing strategy, with “hosts” (householders) providing housing support for “guests” living in their home. Yet, understanding children's experiences in doubled-up households requires attention to host/guest status. Using the American Community Survey and Survey of Income and Program Participation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…In particular, these populations are also at higher risk of chronic health problems aggravating the clinical course of COVID-19, including diabetes, heart disease and obesity ( 6 , 40 ). Here, we concentrated on genetic variants that affect the African/Latino American ethnicities, also facing the greatest socioeconomic and racial disparities ( 41 ). Structural studies have reported numerous genetic variations affecting the stability of the ACE2 - SARS-CoV-2-S complex ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these populations are also at higher risk of chronic health problems aggravating the clinical course of COVID-19, including diabetes, heart disease and obesity ( 6 , 40 ). Here, we concentrated on genetic variants that affect the African/Latino American ethnicities, also facing the greatest socioeconomic and racial disparities ( 41 ). Structural studies have reported numerous genetic variations affecting the stability of the ACE2 - SARS-CoV-2-S complex ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…A housing affordability crisis may threaten people's ability to establish and/or maintain independent households (Choi 2003;Goldscheider and Goldscheider 1999;Keene and Batson 2010). When they learn that a family member is having difficulty paying for adequate and suitable housing, family members may "double up" as a way to offer housing assistance to the member in need or pool resources to cover the rent or mortgage (Cross 2018;Harvey, Dunifon, and Pilkauskas 2021;Li and Wu 2019;Pilkauskas 2012). How multigenerational living shapes children's odds of living in unaffordable housing will largely depend on the function of multigenerational households (Harvey et al 2021).…”
Section: Housingmentioning
confidence: 99%
“…When they learn that a family member is having difficulty paying for adequate and suitable housing, family members may "double up" as a way to offer housing assistance to the member in need or pool resources to cover the rent or mortgage (Cross 2018;Harvey, Dunifon, and Pilkauskas 2021;Li and Wu 2019;Pilkauskas 2012). How multigenerational living shapes children's odds of living in unaffordable housing will largely depend on the function of multigenerational households (Harvey et al 2021). If multigenerational co-residence serves as a vehicle to support children and their parents or a system of interdependence to offer mutual support to all parties, multigenerational living will be associated with lower odds of living in unaffordable housing.…”
Section: Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the literature on co‐residence has focused on the increasing propensity of children to live with grandparents or older adults (for example, Harvey et al, 2021; Pilkauskas et al, 2020; Pilkauskas & Cross, 2018). Though less pronounced than changes in child living arrangements, there have also been changes in the residential patterns of seniors.…”
Section: Introductionmentioning
confidence: 99%